Bearing witness against unbearable whiteness: Lessons from Luther for confronting racism today. Issue 2 (8th May 2021) - Bateza, Anthony
Abstract: Anti‐black racism has a long history in the United States, and while its presence is constant its ramifications are manifold. This means that careful attention, prudent discernment, and diligent action are required if we are to confront racism today. In this article I examine the obstacles that whiteness creates when it comes to recognizing the testimony of Black people. My claim is that white peoples in general, and Lutherans in particular, suffer from either a persistent inability or cultivated unwillingness to receive Black witness. I begin by briefly discussing Martin Luther's views on bearing witness, highlighting the theological and practical importance of this work within a Lutheran theological heritage. Next, I proceed to the ways that witness is compromised, the conditions that undermine the giving and receiving of testimony. Drawing on insights from Rebecca Kukla, Miranda Fricker, and others, I frame these compromises as instances of discursive and epistemic injustice, as harms done to Black subjects as their white counterparts fail to take up offerings of truth and extend trust. Finally, I conclude by suggesting some Lutheran theological and practical opportunities for resistance and retraining, so that anti‐racist work might be embodied more fully in spaces filled with whiteness.